Effect of Foundation Width on Subgrade Reaction Modulus - Nagao, T. (Engineering, Technology & Applied Science Research, 2020)
Structures are subjected to vertical and horizontal loads. Vertical subgrade reaction acts on the foundation bottom surface, and in the case of an embedded structure, horizontal subgrade reaction acts on the embedded part. The subgrade reaction is obtained by multiplying the displacement of the foundation by the Subgrade Reaction Modulus (SRM). In practice, SRM is calculated using an equation that incorporates the negative power relationship of the Foundation Width (FW). If the structure is evaluated to be poorly seismic resistant, it is necessary to widen FW. However, when the FW is widened, the design value of SRM decreases. In this case, it is not possible to expect an increase in the subgrade reaction proportional to the increase of FW. Therefore, when the inertia force is very high, the FW has to be very wide. However, underestimating SRM can lead to structural overdesign. In this study, the relationship between SRM and FW, for a structure in which vertical and horizontal load act simultaneously, was analyzed. Compared with the design practice assumptions, the horizontal SRM was found to be highly dependent on FW while the vertical SRM was shown to be less dependent on FW.